دراسة مخبرية مقارنة لتأثير ثلاث أنواع مختلفة من الإسمنت على ثبات واستقرار تيجان أكسيد الزيركون - عيسى نزيه; بهرلي ناصر; رفاعي عمر (Latakia University Journal -Medical Sciences Series, 2019)
تهدف هذه الدراسة لتحديد الإسمنت الأفضل لإلصاق تيجان الزيركونيا, ومن أجل ذلك تم تحضير 48 رحى مقلوعة حديثاً بسطح إطباقي مستو ودرجة ميلان 6ْ و طول محوري 3ملم تقريباً, ثم تم حساب مساحة السطح الإطباقي والسطوح الجانبية لكل سن محضر ثم وزعت إلى ثلاث مجموعات بشكل متساو لكل من اختبارات الثبات والاستقرار . تم عمل البنى الهيكلية الزيركونية للأسنان المحضرة مع قضيب إطباقي (مجموعات الثبات) ودهليزي (مجموعات الاستقرار) لتسهيل نزعها خلال إجراء الاختبارات وذلك باستخدام نظام cad/cam مع ترميل السطح الداخلي للهياكل الزيركونية بحبيبات أكسيد الألمنيوم 50 ميكرون . تم إلصاق الأسنان باستخدام ثلاث اسمنتات هي الزجاجي الشاردي ( fuji 1 ) والزجاجي الشاردي المعدل بالراتنج ( fuji cem ) والراتنج ذاتي الإلصاق ( G-cem ) . تم نزع الهياكل الزيركونية الملصقة بالاسمنتات باستخدام جهاز الاختبارات الميكانيكية العام بسرعة 5 ملم / الدقيقة, وتم تسجيل قوة النزع ثم حساب الإجهاد حسب مساحة السطح لكل سن محضر . خلصت الدراسة إلى وجود فرق بين قيم الثبات والاستقرار لتيجان الزيركونيا الملصقة بالزجاجي الشاردي مقارنة مع التيجان الملصقة بالزجاجي الشاردي المعدل بالراتنج والراتنج ذاتي الإلصاق التي أعطت قيماً أكبر, بينما لم يظهر أي فروق معنوية بين تأثير الزجاجي الشاردي المعدل بالراتنج والراتنج ذاتي الإلصاق على ثبات واستقرار تيجان الزيركونيا . The aim of this study is to determine the ability of selected luting agents to retain a zirconium oxide ceramic crown. However, 48 recently extracted human molars will be prepared with a flat occlusal surface, 6-degree taper, and approximately 3-mm axial length. The axial and occlusal surface areas will be determined, and specimens will be distributed equally by total surface area into 3 cementation groups to every retention and resistant groups. Zirconium oxide ceramic copings with an occlusal bar (retention groups) an buccal bar (resistant groups) to facilitate removal will be fabricated using computer-aided design/computer-assisted manufacturing (CAD/CAM) technology. Copings will be airborne-particle abraded with 50-mum Al2O3 particles. They will then be cemented, using either a self adhesive resin cement (G-cem , fuji group), glass ionomer cement (fuji 1), Resin-modified glass-ionomer (fuji cem). The cemented copings will be removed using a universal testing machine at 5 mm/min. The removal force will be recorded, and the stress of dislodgement is calculated using the surface area of each preparation. In conclusion, there are differentiation between effectiveness of glass ionomer cement on retention and resistant of zirconia crown compare with effectiveness of Resin-modified glass-ionomer and self adhesive resin cement, but there are no differentiation between effectiveness of Resin-modified glass-ionomer and self adhesive resin cement on retention and resistant.